Dendrochronology and growth of Copaifera langsdorffii wood in the vegetation dynamics of the Pirapitinga Ecological Station, state of Minas Gerais, Brazil - Carvalho, Daniel Costa de; Pereira, Marcos Gervasio Gervasio; Carmo, Jair Figueiredo do; Pace, José Henrique Camargo; Silva, Leonardo Davi Silveira Augusto Baptista da; Latorraca, João Vicente Figueiredo (Floresta, 2018)
This study aims to build a chronology of the growth rings of Copaifera langsdorffii (copaíba) in order to understand the dynamics of vegetation types that occur on a river island in the Cerrado biome. For this purpose, we selected 30 trees of copaíba established in a vegetation of Mata Seca Sempre-Verde in the Pirapitinga Ecological Station (EEP), state of Minas Gerais, Brazil. Two radial samples from each tree were collected by an auger. The samples were treated by mechanical polishing for better visualization of the growth rings, and consequently further delineation and measurement. Later, the width of the growth rings was verified in order to generate a master time series of the specie. To check the influence of meteorological factors, we used the Pearson correlation (p < 0.05). The results showed that the population of copaíba in the EEP presented dendrochronologyc potential, which was confirmed by the high values of wide growth rings correlation within and between trees. The dendrochronologyc analysis revealed that copaíba trees were already present before the dam filling, but with lower population density than today. It was also possible to infer that the development of the vegetation type Mata Seca Sempre-Verde occurred since the decade of the 1970. The average sensitivity was enough to consider the species sensitive to environmental variations. Precipitation and temperature only influenced positively the growth rings in the transition from dry to wet seasons. The results revealed information about the dynamics of the local vegetation, elucidating the changes that occurred in the environment in which the population of copaíba is established.